1992
DOI: 10.1159/000294862
|View full text |Cite
|
Sign up to set email alerts
|

Could Bacterial Vaginosis Be Due to the Competitive Suppression of Lactobacilli by Aerobic Microorganisms?

Abstract: Bacterial vaginosis (BV) is characterized by lack of lactobacilli and predominance of anaerobic species. Ciprofloxacin is active against a great number of aerobic bacteria. The effect of ciprofloxacin on the vaginal microbial flora was studied both in healthy subjects and in patients with BV in order to test if BV may be due to competitive suppression of lactobacilli by aerobic species. About half of the patients were relieved of their symptoms. No adverse effects on the microbial profile or colonization by la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These GI and vaginal commensalisms confer significant health benefits upon the host organism through a barrier effect by preventing access to these regions by transient pathogens (9,23). Indeed, a delicate quantitative balance of vaginal yeasts is maintained and limited by Lactobacillus species, presumably through peroxide production (24,33). To this end, live microbes are being marketed and actively consumed as probiotic supplements to alleviate or prevent certain GI tract disorders and vaginal yeast and urinary tract infections (23,33).…”
mentioning
confidence: 99%
“…These GI and vaginal commensalisms confer significant health benefits upon the host organism through a barrier effect by preventing access to these regions by transient pathogens (9,23). Indeed, a delicate quantitative balance of vaginal yeasts is maintained and limited by Lactobacillus species, presumably through peroxide production (24,33). To this end, live microbes are being marketed and actively consumed as probiotic supplements to alleviate or prevent certain GI tract disorders and vaginal yeast and urinary tract infections (23,33).…”
mentioning
confidence: 99%
“…3A ). Despite there being few reports of two of the lineages ( L. reuteri and L. plantarum ) in the vagina ( 23 , 24 ), the first 7 lineages were previously often reported as occurring in the human vagina and were widely thought to be associated with the vaginal microbiota ( 25 , 26 ). In the study, we identified an additional 2,200%, 33%, 20%, 6%, 643%, 19%, and 50% novel sequence/reference sequence in these 7 lineages, which may be considered new reference sequences for the present database ( Fig.…”
Section: Resultsmentioning
confidence: 99%